Consumer Participation in the Creation of a Tourist Product - Nawrocka, Elżbieta; Niezgoda, Agnieszka (Studia Oeconomica Posnaniensia, 2017)
The purpose of the article is an analysis of the characteristics of a consumer participating in the creation of products, the so-called prosumers, as well as an analysis of factors facilitating such participation on the part of tourist enterprises. The discussion covers the tourist market. The method is a review of subject literature discussing the category of a prosumer from the perspective of a tourist market along with the authors' interpretation. Categorized direct interviews with managers and employees having direct contact with customers in hotels and travel agencies, presenting appropriate experience (several years of work), were used in the empirical part. The research is of qualitative, explorative nature. In the article the category of a tourist market prosumer was defined and the changed CRM formula was suggested - customer relations management into CMR i.e. consumer management relations in the conditions of the discussed market. The exploratory analysis showed the stereotypical thinking about a customer, who is treated as: an offer purchaser and the source of information about his/her needs and expectations. The collected suggestions and opinions are used to construct customers' involvement in the business issues of the studied companies, including the creation of new value. The article is of an empirical nature and represents a review in its theoretical part.